Determination of Three Detergent Products and Identification of Surface Active Agents by Infrared Absorption Spectra and a Reflectance Graph - Katerina Chryssou; Maria Stassinopoulou; Eugenia Lampi (Challenges and Advances in Chemical Science Vol. 8, 2022)
Three types of commonly used detergents (i.e. detergent for all surfaces Ajax Fête des Fleurs by Colgate Palmolive, dishwashing detergent maki by Alinda Velco, limescale remover spray Nuevo Kiriko antical made by Casa Kiriko S.L. Spain) have been analyzed with the mixed indicator titration method which made use of the mixed indicator dimidium bromide/disulphine blue. Also the use of infrared spectroscopy for qualitative identification of the anionic and non-ionic surfactants present in them was reported. Diffuse reflectance spectra (DRS) analysis was applied for the third detergent product. From the diffuse reflectance spectra the band gap energy (Eg) of the material has been estimated. This method has been investigated with a single integrating sphere system over the visible wavelength range. This study aimed to identify and quantify three commonly used detergents for quality control, and for the surfactants characterization as to their spectral properties, and structural state, for potential membrane protein solubilization.